2017
DOI: 10.1002/joc.5387
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal variability of daily precipitation concentration in Spain based on a high‐resolution gridded data set

Abstract: An analysis of the spatial and temporal variability of daily precipitation concentration (CI) in Spain was made based on a high‐resolution (5 × 5 km) daily gridded precipitation data set for the 1950–2012 period. For each grid point in the Iberian Peninsula (IP) and Balearic and Canary Islands, the average annual CI was computed, as well as its coefficient of variation and the 5th and 95th percentiles. Annual values were also computed, and the time series of the index were used to assess temporal trends over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 44 publications
4
59
1
2
Order By: Relevance
“…Even if these four indices show clear advantages, as a deeper knowledge of daily behaviour of precipitation, they also exhibit some limitations. Precipitation trends present a great uncertainty due to the use of different data sets (DMC and DGA), periods, and climatic regions, and it is exacerbated when analysing trends in precipitation indices (as those presented here) that needs a daily resolution for its calculation (Serrano‐Notivoli et al, ). Moreover, fractal dimension D does not consider the amount of precipitation registered in each interval.…”
Section: Discussioncontrasting
confidence: 99%
“…Even if these four indices show clear advantages, as a deeper knowledge of daily behaviour of precipitation, they also exhibit some limitations. Precipitation trends present a great uncertainty due to the use of different data sets (DMC and DGA), periods, and climatic regions, and it is exacerbated when analysing trends in precipitation indices (as those presented here) that needs a daily resolution for its calculation (Serrano‐Notivoli et al, ). Moreover, fractal dimension D does not consider the amount of precipitation registered in each interval.…”
Section: Discussioncontrasting
confidence: 99%
“…No relation was found between the mean annual rainfall values and CI and n or . Similar results were obtained for Spain (Martin-Vide, 2004;Serrano-Notivoli et al, 2018), Italy (Coscarelli and Caloiero, 2012) and Turkey (Yeşilırmak and Atatanir, 2016). The results have indicated that in each of the years for which the precipitation concentration falls within the strong irregular range, the values of CI and n or (>0.66-0.60, respectively) correspond approximately to 75% of the precipitation being contributed by 25% of the rainiest days.…”
Section: Spatial Distribution Of Daily Precipitation Concentration supporting
confidence: 78%
“…Significant negative correlations were detectable between the number of rainy days and both CI and n or throughout the MR ( r = −0.50, r = −0.35, p < .05), respectively, so the higher rainfall concentrations are observed in the areas with fewer rainy days. No relation was found between the mean annual rainfall values and CI and n or . Similar results were obtained for Spain (Martin‐Vide, ; Serrano‐Notivoli et al ., ), Italy (Coscarelli and Caloiero, ) and Turkey (Yeşilırmak and Atatanir, ). The results have indicated that in each of the years for which the precipitation concentration falls within the strong irregular range, the values of CI and n or (>0.66–0.60, respectively) correspond approximately to 75% of the precipitation being contributed by 25% of the rainiest days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CI values calculated in the present work (0.477÷0.723) fall within the range (0.38÷0.87) obtained in a global analysis by Monjo and Martin‐Vide (); they are similar to the ones computed in several studies on the whole of Europe (Cortesi et al, ) or at national and sub‐national scale in the Mediterranean basin (Italy—Coscarelli and Caloiero, ; Algeria—Benhamrouche et al, ; Spain—Serrano‐Notivoli et al, ). Moreover, these results agree with the ones obtained in several world countries such as the United States (Royé and Martin‐Vide, ), New Zealand (Caloiero, ) and Chile (Sarricolea et al, ).…”
Section: Resultsmentioning
confidence: 96%